Two Haplotypes of Capsella Bursa-Pastoris (Brassicaceae) in Continental Chile Support Multiple Introduction [Dos Haplotipos de Capsella Bursa-Pastoris en Chile Continental Soportan Multiple Introducción] - Castro-Morales, S; Espinosa-Mendez, C (Universidad de Concepcion, 2014)
Shepherd’s purse (Capsella bursa-pastoris; Brassicaceae) is a global weed. In Chile, this species was introduced early during Spanish colonization, however, previous studies based on allozymes and RAPD fragments, show that populations in southernmost Chile could be related to England populations. Here, we analyze the geographical variation of three sequences of cpSSR in 286 individuals of C. bursa-pastoris (ATCP46615, ATCP66701 and ATCP31017). We collected plants from 14 populations distributed over a wide latitudinal gradient in continental Chile. Only one of the markers showed variation (ATCP31017), evidencing the presence of two haplotypes along the territory. The geographic distribution of these haplotypes support previous studies based on allozymes and RAPD fragments, suggesting that C. bursa-pastoris in continental Chile was introduced at least twice. © 2014, Universidad de Concepcion. All rights reserved.